Regime-dependent commodity price dynamics: A predictive analysis - Jesús Crespo Cuaresma; Ines Fortin; Jaroslava Hlouskova; Michael Obersteiner (Institut für Höhere Studien - Institute for Advanced Studies (IHS), 2021)
We develop an econometric modelling framework to forecast commodity prices taking into account potentially different dynamics and linkages existing at different states of the world and using different performance measures to validate the predictions. We assess the extent to which the quality of the forecasts can be improved by entertaining different regime-dependent threshold models considering different threshold variables. We evaluate prediction quality using both loss minimization and profit maximization measures based on directional accuracy, directional value, the ability to predict adverse movements and returns implied by a trading strategy. Our analysis provides overwhelming evidence that allowing for regime-dependent dynamics leads to improvements in predictive ability for the Goldman Sachs Commodity Index, as well as for its five sub-indices (energy, industrial metals, precious metals, agriculture, livestock). Our results suggest the existence of a trade-off between predictive ability based on loss and profit measures, which implies that the particular aim of the prediction exercise carried out plays a very important role in terms of defining which set of models is the best to use.
Keywords: Q02; C53; F47; 330; Commodity prices; forecasting; threshold models; forecast performance; states of economy